1976
DOI: 10.1017/s0043174500066558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Metribuzin Activity in the Soil

Abstract: Metribuzin [4-amino-6-tert-butyl-3-(methylthio)-as-triazine-5(4H)one] applied preemergence resulted in increased phytotoxicity with increasing soil pH. In the field, fall panicum (Panicum dichotomiflorumMichx.) control, number of dead corn (Zea maysL.) and soybean [Glycine max(L.) Merr.] plants, and crop injury ratings increased, and plant height and grain yield decreased as the soil pH increased. In the greenhouse, corn and soybean grown in soil showed decreased dry weights due to metribuzin as pH increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 10 publications
4
39
0
Order By: Relevance
“…This agrees with Ladlie et al (14) who showed that the activity of metribuzin was significantly less at pH 4.6 than at 6.7. In the opinion of Bailey and White (5) the surface pH level is probably the most important soil property in determining the activity of basic organic compounds such as metribuzin.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with Ladlie et al (14) who showed that the activity of metribuzin was significantly less at pH 4.6 than at 6.7. In the opinion of Bailey and White (5) the surface pH level is probably the most important soil property in determining the activity of basic organic compounds such as metribuzin.…”
Section: Introductionsupporting
confidence: 93%
“…Considerable work has shown that many herbicides exhibit better activity at higher soil pH, particularly the triazines (12,13,14) and dinitroanilines (9,10,11,15). Hartwig (8) found with atrazine and simazine that control of fall panicum (Paniem dicotomiflorm Michx.)…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the level of barley damage reported between Warooka and Rudall locations at the highest rate of metribuzin (270 g/ha) are likely to be due to lower clay and organic matter content at Rudall (Table 1). These soil characteristics have been shown to be associated with increased metribuzin activity and crop phytotoxicity (Ladlie et al 1976;Blackshaw et al 1994). In contrast, the heavy textured soil at Warooka is likely to adsorb and bind more metribuzin, reducing its influence on the crop.…”
Section: Resultsmentioning
confidence: 99%
“…Sorption to soil also influences herbicide soil mobility. As a herbicide becomes sorbed to soil colloids, it generally becomes less mobile in the soil . Uncharged herbicides with high water solubility and low K ow tend to be poorly sorbed to soil and are therefore more mobile owing to their greater affinity for the water phase.…”
Section: Introductionmentioning
confidence: 99%